Psicose e delírio em um centro de atenção psicossocial: o caso W - Mangolini, Bruno Benndorf (2018)
This paper presents a case that was treated at a Psychosocial Care Center in the city of São Paulo. The study raises pertinent questions to the clinical point of view, considering the challenge of acting in cases of delusional patients. The case is presented since his arrival at the institution, when referral information was initially discussed in psychiatric terms, which addresses the history and evolution of nomenclature. The research reveals the difficulties of adherence to the treatment, as well as the strategies for the binding process. Then, the first consultations and the impressions of the researcher are presented, which starts to seek references for clinical care. The psychoanalytic conceptions of psychosis and delirium and how they could contribute to the care in question are discussed. Finally, we use the schizoanalytic reference, through concepts such as machine, agency and body without organs, to point out another way of thinking and acting in the case